2014
DOI: 10.1098/rspb.2014.0873
|View full text |Cite
|
Sign up to set email alerts
|

The link between behavioural type and natal dispersal propensity reveals a dispersal syndrome in a large herbivore

Abstract: When individuals disperse, they modify the physical and social composition of their reproductive environment, potentially impacting their fitness. The choice an individual makes between dispersal and philopatry is thus critical, hence a better understanding of the mechanisms involved in the decision to leave the natal area is crucial. We explored how combinations of behavioural (exploration, mobility, activity and stress response) and morphological (body mass) traits measured prior to dispersal were linked to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 61 publications
1
23
0
Order By: Relevance
“…Long‐term studies in roe deer showed bold animals were more likely to disperse and that ‘boldness’ was strongly positively correlated with other behavioural measures, including habitat selection (Debeffe et al . ; Bonnot et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long‐term studies in roe deer showed bold animals were more likely to disperse and that ‘boldness’ was strongly positively correlated with other behavioural measures, including habitat selection (Debeffe et al . ; Bonnot et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Probability of individual female elk switching between migratory strategies from year t À 1 to t as a function (a) elk abundance in the previous winter (t À 1), and (b) spring and summer precipitation in the preceding summer, t À 1, and (c) individual age (as estimated from cementum annuli) at t for migrant (red) and resident (blue) elk in the Ya Ha Tinda elk population, Alberta, Canada, 2002-2012 behaviour may be a behavioural syndrome in ungulates, as in other taxa (Nilsson 2010;Chapman et al 2011b). Long-term studies in roe deer showed bold animals were more likely to disperse and that 'boldness' was strongly positively correlated with other behavioural measures, including habitat selection (Debeffe et al 2014;Bonnot et al 2015). Further work is needed to test whether migration is a behavioural syndrome, and what the consequences are for conservation.…”
Section: Discussionmentioning
confidence: 99%
“…Research into dispersal of roe deer ( Capreolus capreolus ) reported that future dispersers had greater energetic budgets compared to future philopatric fawns (Debeffe et al ), had larger antlers (Wahlstörm ), and were heavier (Wahlstörm and Liberg ). Yearling male white‐tailed deer with larger antlers may also disperse more than those with relatively small antlers (McCoy et al , Shaw et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The seasonality of dispersal timing we observed may suggest strong male-male competition in the study area (Rosenberry et al 1999), with limited female aggression towards yearling males. Research into dispersal of roe deer (Capreolus capreolus) reported that future dispersers had greater energetic budgets compared to future philopatric fawns (Debeffe et al 2014), had larger antlers (Wahlstörm 1994), and were heavier (Wahlstörm and Liberg 1995). Yearling male white-tailed deer with larger antlers may also disperse more than those with relatively small antlers (McCoy et al 2005, Shaw et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, migratory behaviours of ungulates appear to be culturally transmitted from mother to offspring (Jesmer et al, 2018;Nelson, 1998;Sweanor & Sandegren, 1988), yet the mechanisms underlying cultural transmission are unclear-in part because of the long-term and multi-generational data necessary to understand them (Gaillard, 2013). Flexibility in both propensity to migrate (Eggeman et al, 2016;Fieberg et al, 2008) and natal dispersal (Debeffe et al, 2014;Wahlström & Liberg, 1995) can be important pathways to the development of migratory behaviour in some ungulates (Cote et al, 2017). In lieu of random dispersal, however, inheritance of a migratory route by the offspring from the mother implicitly transfers a successful migratory tactic to the offspring (Harrison et al, 2010).…”
Section: Plasticity Of Migratory Behaviour Including Decisions Aboutmentioning
confidence: 99%